Definition of road roughness parameters for tire vibration noise control - Fujikawa, Tatsuo; Koike, Hiroshi; Oshino, Yasuo; Tachibana, Hideki (Applied acoustics, 2005)
Road roughness plays an important role in the generation of tire vibration noise. However, it is unclear which kinds of road roughness parameters should be controlled to reduce the noise. In this paper, we define the essential road roughness parameters that govern tire tread vibration and provide information on tire/road noise abatement. The detailed effects of road roughness parameters on tire tread vibration are estimated using a tire/road contact model. The results reveal that pavement asperity height itself is not an essential parameter, but asperity height unevenness, asperity radius, and asperity spacing are important for the abatement of tire vibration noise.